2020
DOI: 10.1039/d0gc00096e
|View full text |Cite
|
Sign up to set email alerts
|

Spherical lignin particles: a review on their sustainability and applications

Abstract: A critical review on spherical lignin nanoparticles highlighting aspects associated to their shape, performance in applications, sustainability, stability and degradation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
224
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 284 publications
(249 citation statements)
references
References 188 publications
(285 reference statements)
3
224
0
Order By: Relevance
“…Nanolignin could be prepared via precipitation technology [ 108 ], ultra-sonication [ 109 ], atomization [ 110 ], high shear homogenization [ 111 ] and continuous solvent exchange/dialysis for various applications [ 112 ]. The techniques used to prepare lignin nanoparticles could be also divided into wet and dry methods [ 113 ]. Wet particles are generally produced via various precipitation methods which involve a process of dissolving lignin in organic solvent and a process of precipitating in an anti-solvent (typically water).…”
Section: Preparation Of Lignin Nanoparticles and Their Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanolignin could be prepared via precipitation technology [ 108 ], ultra-sonication [ 109 ], atomization [ 110 ], high shear homogenization [ 111 ] and continuous solvent exchange/dialysis for various applications [ 112 ]. The techniques used to prepare lignin nanoparticles could be also divided into wet and dry methods [ 113 ]. Wet particles are generally produced via various precipitation methods which involve a process of dissolving lignin in organic solvent and a process of precipitating in an anti-solvent (typically water).…”
Section: Preparation Of Lignin Nanoparticles and Their Applicationmentioning
confidence: 99%
“…For example, it was reported that lignin fractions with high molecular weight, low content of OH groups and high S/G ratio resulted in weak lignin–water interactions and a high degree of aggregation, thereby resulting in a small size of nanoparticles [ 118 ]. Although lignin particles are generally considered non-toxic by in vitro or in vivo toxicological assessment, the current production of lignin nanoparticles often requires the use of organic solvents and thus can generate toxic effects on the environment [ 113 ]. In addition, some of the processes also use expensive materials.…”
Section: Preparation Of Lignin Nanoparticles and Their Applicationmentioning
confidence: 99%
“…Healthcare, food, civil construction, and agriculture greatly benefit from dispersants that enable the mixing of immiscible liquid phases and enhance the stability of particle suspensions. Dispersants lower the interfacial tension between immiscible liquids, as well as increasing the repulsive forces between suspended particles and prevent settling and aggregation of phases, thus improving technical properties of multiphase systems such as rheology, lifetime, and function [ 97 ].…”
Section: Lignin Applicationsmentioning
confidence: 99%
“…The majority of the industrially used dispersants are synthesized from non-renewable precursors and are not biodegradable, raising concerns over their sustainability [ 97 ]. Therefore, the development of lignin-based dispersants is an attractive solution.…”
Section: Lignin Applicationsmentioning
confidence: 99%
“…Indeed, LNPs display fascinating properties such as favorable dispersibility, high specific surface area, and flexible molecular design [ 14 ]. They aid in the preparation of nanostructured materials with several enhanced properties including increased thermal stability, mechanical performance, and barrier properties [ 15 , 16 , 17 ]. Despite this promising potential, large-scale production of LNPs is far from sufficient.…”
Section: Introductionmentioning
confidence: 99%